The freshwater ichthyofauna of Greece - an update based on a hydrographic basin survey - ECONOMOU, A.N.; GIAKOUMI, S.; VARDAKAS, L.; BARBIERI, R.; STOUMBOUDI M.ΤΗ.; ZOGARIS, S. (Mediterranean Marine Science, 2007)
Distribution records (historical, contemporary) for native and non-native freshwater fish species from 105 hydrographic basin areas were compiled and analysed in order to develop a nation-wide inventory (including transboundary river basins). Overall, 162 species, including diadromous and euryhaline, with documented occurrence records in freshwaters, and taxa of unclarified taxonomic status, are accommodated in the distributional compilation. An annotated checklist summarises the confirmed ichthyofauna of Greek freshwaters (161 species); a provisional supplementary list contains species recorded in brackish waters (55 species). In comparison to the last published (1991) checklist of freshwater fish of Greece, the present checklist shows an increase in species number of 53% (56 species). This increase has resulted mainly from taxonomic re-evaluations of existing taxa on the basis of new information and adoption of a new systematic concept. The current trend, as reflected in recent ichthyological publications, is towards abandonment of the biological species concept (BSC) and adoption of the phylogenetic species concept (PSC) for the delineation of species boundaries. The practical implications of the change in species concept on biodiversity conservation and watershed management are discussed. An overview of the composition and characteristics of the freshwater fish fauna of Greece is provided, especially with regard to the native and introduced status of species, and the spatial patterns of species richness and endemism. This systematic inventory may assist in efforts to develop nation-wide surface water bioassessment tools within the demands of the Water Framework Directive (WFD); it may further promote biodiversity conservation and biologically-orientated fishery management approaches.